Prekinitveni post - moder ali zgolj moderen? - Petravić, Luka (Medicinski razgledi, 2022)
The beginnings of intermittent fasting reach thousands of years ago. Many health conditions that not only complicate an individual’s daily life but also pose a major public health problem are addressed with pharmacological interventions; in addition to that, other types of less invasive interventions that would aid treatment have also been explored in recent years. Fasting presents an economical and efficient intervention for the improvement of many pathological states, including, but not limited to, hypertension and other cardiovascular diseases, diabetes, stress related psychopathology, etc. There are many regimes of intermittent fasting, which are more (multiday) or less (one day) radical. In recent years, a lot of evidence has accumulated about the positive effect of intermittent fasting. This has been done at the basic research level (cells and tissues), even though many intermittent fasting mechanisms are yet to be completely uncovered. A lot of damage has been done, especially to the general population, due to misinformation that are completely wrong and not in the readers’ best interest. This has been the greatest motivation for this review of intermittent fasting in the Slovenian language. Its aim is to be understandable to people who want to know more but lack advanced education to properly review the literature themselves. We present different styles of intermittent fasting, their effects on individual organs, and potential use of intermittent fasting in disease.
Keywords: hipertenzija; kardiovaskularne bolezni; kognicija; mikrobiota; post; prehrana; prekinitveni post